Digital Culture and Psychopolitics in Waheed Ahmed’s The Black Hill Syndrome: A Post-9/11 Story - Muhammad Rehan Sabir; Abdillah Nugroho (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This study examines how Waheed Ahmed’s The Black Hill Syndrome (2024) allegorizes digital culture as a system of hidden domination. Drawing on Baudrillard’s theory of hyperreality and Han’s concept of psychopolitics, this study argues that both Black Hill and digital culture simulate freedom while sustaining a complex system of control. In the post-9/11 context, the novel reflects cultural anxieties around surveillance, identity, and authority. Black Hill serves as a metaphor for digital culture, as it conceals power relations behind openness and autonomy. The paper analyzes digital hegemony as a modern continuation of imperialist agendas. What is presented as free expression is in fact a carefully managed illusion that preserves capitalist structures. By examining the erasure of individuality, the suspension of time, and the unseen authority of “Mundri Wala” in Black Hill, the study demonstrates how both Black Hill and digital culture create the performance of freedom while diffusing real autonomy. This study also explores how Pakistani fiction not only reflects post-9/11 anxieties but also engages with global debates on digital control, autonomy, and resistance.